(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2016)
Coastal settlement of Banda Aceh in the north of Sumatera Island has high potential risk of tsunami disaster. In the year 2004, half of Banda Aceh city has been destroyed by tsunami disaster, especially its coastal settlement area. Based on this experience, the approach of disaster mitigation concept for coastal settlement with vision of environment represent wise choice on planning sustainable Banda Aceh for future generation. This qualitative research try to explore the role of green open space as green structure of the city by considering aspect of tsunami disaster mitigation for coastal settlement of Banda Aceh. This research will evaluate the existence of green open space and post disaster reconstruction of coastal settlement area. Result of this research is green structure concept in coastal settlement of Banda Aceh based on tsunami disaster mitigation and expected to contribute ideas for disaster mitigation in other coastal settlement areas.